A Research on Financial Performance of Indian Companies under Corporate Governance: Examining the Relationship between Corporate Governance and Financial Performance of Indian Companies (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Corporate Governance is expected to make a corporate culture of cognizance, straightforwardness and transparency. It empowers a company to augment the long haul value of the company which is found regarding performance of the company. In this paper, we take a gander at different Corporate Governance practices pursued by companies in India Constitution, Board Structure, Different Committees, Independent Directors and their jobs, Conflict of interest and Disclosure of data. The goal is to decide whether there is a connection between corporate governance and company performance. The ponder attempts to see whether higher and better corporate governance prompts better performance of the companies. It is found in the consider that corporate governance practices have constrained effect on both the offer costs of the companies just as on their financial performance.